Web Retrieval, Ranking and Personalization - Teevan, Jaime; Dumais, Susan; White, Ryen W. (Interactive Information Seeking and Retrieval, 2011)
Most books on information-seeking neglect the human side to focus solely on the technical aspects of retrieval systems. This book is the first to provide an information science perspective on information retrieval, with a focus on user behavior and needs. Beginning with the history of information retrieval, coverage goes on to consider behavioral models and interactive techniques as well as the design, implementation and evaluation of information retrieval interfaces. This comprehensive book will be the go-to for LIS students and professionals hoping to better appreciate and utilize information retrieval systems, theories, and practices. Contents Interactive information retrieval : history and background / Colleen Cool and Nicholas J. Belkin Information behavior and seeking / Peiling Wang Task-based information searching and retrieval / Elaine G. Toms Approaches to investigating information interaction and behaviour / Raya Fidel Information representation / Mark D. Smucker Access models / Edie Rasmussen Evaluation / Kalervo Järvelin Interfaces for information retrieval / Max Wilson Interactive techniques / Ryen W. White Web retrieval, ranking and personalization / Jaime Teevan and Susan Dumais Recommendation, collaboration and social search / David M. Nichols and Michael B. Twidale Multimedia : behaviour, interfaces and interaction / Haiming Liu, Suzanne Little and Stefan Rüger Multimedia : information representation and access / Suzanne Little, Evan Brown and Stefan Rüger